The relationships of forest and watershed characteristics to soil water retention, storm runoff, erosion, and wave attenuation in Vietnam - Tran, Bao Quang, author; Laituri, Melinda J., advisor (Colorado State University. Libraries, 2009)
Forests can have a profound impact on the hydrological cycles. Numerous studies in Vietnam, and elsewhere have examined the effects of vegetation cover and geomorphology on hydrological processes at both watershed and regional scales, but the effects of forests in water yield, regulating seasonal water flows, and soil erosion are still in debate. This dissertation focuses on obtaining a deeper understanding about how forests, weather and geomorphology affect hydrological responses and soil erosion in Vietnam. Dissertation is a collection of four independent studies. The first study characterizes soil water retention of four forest types representing different levels of forest degradation. The results suggest that soil water retention, a function of soil moisture, bulk density, and soil depth; varies among forests, and it depends primarily on litter cover, vegetation cover, and porosity. Forest soil moisture can be predicted by a regression model, with the root square mean error of 3%. The second study investigates effects of watershed characteristics on runoff in 15 typical watersheds. The watershed factors, which include watershed size, shape, slope and elevation difference, forest cover and distribution, are analyzed in relation to increasing and decreasing peak flow, and daily streamflow variation, in which forest cover and distribution, shape, and elevation difference are found to be significant impacts on storm runoff. Relationships between peak discharge and initial flow and rainfall are statistically significant in this study. The third study is to define minimum forest areas for protection soils from erosion. A soil loss prediction equation and soil loss tolerance of 10 ton ha-1y-1 are used to generate an erosion risk map and vegetation index for Vietnam. Required forest areas are calculated by comparison erosion risk with vegetation index. Finally, wave attenuation is analyzed in relation to initial wave height, cross-shore distances, and mangrove forest structures. From these relationships, minimum mangrove band width for coastal protection from waves is defined and ranges from 40 m to 240 m depending on mangrove structures.
Keywords: erosion; erosion risk map; forest hydrology; soil moisture; Vietnam; watersheds; wave attenuation; hydrologic sciences; forestry